Clinical Characteristics of Minor Hallucinations in Chinese Parkinson's Disease Patients - Zhang, Yu; Zhang, Guo yong; Zhu, Xiao bo; Zhang, Zi en; Gan, Jing; Liu, Zhen guo (Frontiers in Aging Neuroscience, 2022)
Background Psychotic symptoms are common in Parkinson's disease (PD). However, the clinical characteristics of PD psychosis (PDP) have been rarely reported in Chinese PD patients. We aimed to categorize PDP in a PD cohort and its relationship to other clinical characteristics. Methods A total of 149 Chinese PD patients were consecutively enrolled, and idiopathic PD patients were recruited in the study. The symptoms of PDP were assessed with the enhanced Scale for the Assessment of Positive Symptoms in PD. Then, the patients were classified into a PD-control group, isolated minor hallucination (MH) group, and complex MH group, and clinical and demographic data of different groups were compared. Results Parkinson's disease psychosis was present in 40.3% (60/149) of our patients. The most common PDPs were MHs, present in 32.9% (49 of 149) of the cohort. Compared to patients without MHs, patients with MHs were older, had a longer disease duration, a higher levodopa equivalent daily dose, more severe motor symptoms, dyskinesia, a higher rate of rapid eye movement sleep behavior disorders, frontal lobe function impairments, and a higher percentage of cognitive impairment. Logistic regression analysis showed that advanced Hoehn-Yahr stage [odds ratio (OR): 2.697, p = 0.007)] and frontal lobe function impairment (OR: 0.684, p = 0.003) were independent risk factors for MHs. Conclusion MHs were frequent non-motor symptoms in PD patients. It was associated with increased motor and non-motor symptom burdens and reduced quality of life. MHs have been called “minor,” but they have major clinical and prognostic implications and need early screening.